TIK TOK APPLICATIONS TO LEARNING ISLAMIC RELIGIOUS EDUCATION PSYCHOLOGICAL PERSPECTIVE OF ISLAMIC EDUCATION AT SD NEGERI BHAYANGKARA YOGYAKARTA - Adi Wijaya, Bagus; Anis Amanullah, Wahyu; Arfah, M (Proceeding International Seminar of Islamic Studies, 2023)
In quality improvement as well the quality of education, the role of professional teachers is needed to educate the life of the nation. The majority of TikTok application users in Indonesia themselves are millennial, school-age children, or commonly known as generation Z, especially students at SD Negeri Bhayangkara Yogyakarta. With this TikTok application, many people use the TikTok application, especially children who are still in school, especially students at SD Negeri Bhayangkara Yogyakarta, they use it at home. In using it, many students of SD Negeri Bhayangkara Yogyakarta were not positive, such as speaking, bad behavior in each video content. With this in mind, it is necessary to collaborate between schools, Islamic Religious Education Teachers, class teachers and parents of students, so that in the future in using the TikTok application, it is hoped that Islamic Religious Education teachers can utilize this TikTok application for learning Islamic Religious Education to students, so that students can display their skills and creativity in making videos using the TikTok application, such as making videos related to the Asmaul Husna theme where students memorize Asmaul Husna using the tick tok application. The type of research conducted was qualitative research using library research. The purpose of this study is to describe and analyze the patterns and methods of Islamic Religious Education learning carried out using the TikTok application. This TikTok application is used as a learning medium for Islamic Religious Education. TikTok, which is a new social media that is quite popular with the public, has good potential to be used in teaching Islamic Religious Education.